2022
DOI: 10.3892/ijmm.2022.5159
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of Porphyromonas gingivalis into the gingival pocket in mice leads to chronic‑active infection, periodontitis and systemic inflammation

Abstract: Porphyromonas gingivalis (Pg) , one of the 'red-complex' perio-pathogens known to play a critical role in the development of periodontitis, has been used in various animal models to mimic human bacteria-induced periodontitis. In order to achieve a more realistic animal model of human Pg infection, the present study investigated whether repeated small-volume topical applications of Pg directly into the gingival pocket can induce local infection, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…P. gingivalis could be detected in the oral cavity of mice 7 days after P. gingivalis inoculation [ 35 ]. Four weeks and 8 weeks after stopping P. gingivalis topical application in the gingiva of mice, P. gingivalis DNA could still be detected in the oral cavity, suggesting that P. gingivalis can colonize and proliferate in mouse gingiva [ 36 ]. P. gingivalis inoculation in oral cavities of mice leads to elevation of the total cultivatable commensal bacterial load and changes the qualitative composition of oral microbiota [ 35 ], increases oral microbial diversity and allows the colonization of potential opportunistic species [ 37 ].…”
Section: Factors Of Oral Microbiota To Affect Gut Microbiotamentioning
confidence: 99%
“…P. gingivalis could be detected in the oral cavity of mice 7 days after P. gingivalis inoculation [ 35 ]. Four weeks and 8 weeks after stopping P. gingivalis topical application in the gingiva of mice, P. gingivalis DNA could still be detected in the oral cavity, suggesting that P. gingivalis can colonize and proliferate in mouse gingiva [ 36 ]. P. gingivalis inoculation in oral cavities of mice leads to elevation of the total cultivatable commensal bacterial load and changes the qualitative composition of oral microbiota [ 35 ], increases oral microbial diversity and allows the colonization of potential opportunistic species [ 37 ].…”
Section: Factors Of Oral Microbiota To Affect Gut Microbiotamentioning
confidence: 99%
“…In a previous study, we conducted an experiment where we topically applied Porphyromonas gingivalis ( Pg ), an anaerobic Gram-negative bacterium and one of the ‘red-complex’ of periodontal pathogens, into the gingival pockets of wild-type (wt) mice. This led to the development of periodontal disease and resulted in both systemic and vascular inflammation [ 24 ]. Pg releases various bacterial toxins, including lipopolysaccharide (LPS), gingipains, and fimbriae, through local secretion and incorporation into complex outer-membrane vesicles (OMVs) [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous findings demonstrated that the local gingival delivery of Pg LPS induced periodontitis and alveolar bone loss in Apolipoprotein E ( ApoE)- deficient mice, accompanied by elevated levels of local and systemic proinflammatory cytokines [ 22 , 24 , 30 ]. Pg gingipains, cysteine endo-proteases, exert virulent effects by degrading the extracellular matrix, cleaving numerous anti-bacterial proteins in saliva, and provoking systemic inflammation [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported that ligature-induced periodontitis exacerbates atherosclerosis in Apolipoprotein E ( ApoE )-deficient mice [ 14 , 15 , 16 ] and also found that hyperlipidemia is required for the development and progression of atherosclerosis in mice with ligature-induced periodontitis [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%